2011
DOI: 10.1128/iai.00803-10
|View full text |Cite
|
Sign up to set email alerts
|

Burkholderia pseudomalleiProteins Presented by Monocyte-Derived Dendritic Cells Stimulate Human Memory T CellsIn Vitro

Abstract: Melioidosis is a severe infectious disease caused by the saprophytic facultative intracellular pathogen Burkholderia pseudomallei. The disease is endemic in Southeast Asia and Northern Australia, and no effective vaccine exists. To describe human cell-mediated immune responses to B. pseudomallei and to identify candidate antigens for vaccine development, the ability of antigen-pulsed monocyte-derived dendritic cells (moDCs) to trigger autologous T-cell responses to B. pseudomallei and its products was tested. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…However, there is a strong correlation between resolution of clinical melioidosis and T cell response Healey et al;Ketheesan et al;Ramsay et al;Tippayawat et al, 2011). After vaccinating T cell depleted mice with an auxotrophic mutant, Haque et al demonstrated protective responses to B. pseudomallei that were CD4 + , but not CD8 + cell, dependent (Haque et al).…”
Section: Ac-dex Encapsulated B Pseudomallei Antigens Elicit a Robustmentioning
confidence: 95%
See 1 more Smart Citation
“…However, there is a strong correlation between resolution of clinical melioidosis and T cell response Healey et al;Ketheesan et al;Ramsay et al;Tippayawat et al, 2011). After vaccinating T cell depleted mice with an auxotrophic mutant, Haque et al demonstrated protective responses to B. pseudomallei that were CD4 + , but not CD8 + cell, dependent (Haque et al).…”
Section: Ac-dex Encapsulated B Pseudomallei Antigens Elicit a Robustmentioning
confidence: 95%
“…This feature is advantageous for a melioidosis vaccine because there is a strong correlation between the resolution of clinical melioidosis and T cell responses Healey et al;Ketheesan et al;Ramsay et al;Tippayawat et al, 2011), and it is highly likely that cytotoxic T lymphocytes (CTLs) will play an important role in generating a protective immune response (Bondi and Goldberg, 2008;Haque et al, 2006b). CD8 + T cells and natural killer (NK) cells control various pathogens by secreting effector cytokines and cytotolytic granules containing perforin and various granzymes that together disrupt cell membranes and incite apoptotic death (Lauw et al, 2000;Orange and Ballas, 2006;Smith et al, 2009).…”
Section: Introductionmentioning
confidence: 98%
“…Moving forward, it may be prudent to evaluate vaccines with Th1-promoting adjuvants or to use mouse strains that are better capable of eliciting Th1 immune responses, such as C57BL/6 (43). It may also be necessary to enrich the OMV cargo with virulence determinants specific to the intracellular stage of infection (44,45) or with antigens that induce strong T cell responses (46)(47)(48). A number of studies have shown that expression and delivery of homologous and heterologous antigens with OMVs are feasible (45,49,50).…”
Section: Figmentioning
confidence: 99%
“…Despite significant maturation and IL-12 production in bone marrow-derived DC (BMDC) from B. pseudomallei-susceptible BALB/c mice, bactericidal activity against intracellular B. pseudomallei was lower than observed for BMDC from B. pseudomallei-resistant C57BL/6 mice (15). (16,(19)(20)(21)(22).…”
mentioning
confidence: 99%